Strategi Manajemen Sarana Dan Prasarana Pendidikan Agama Islam Dalam Mendukung Proses Belajar Siswa - Winarno, Winarno; Untung, Slamet (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of writing this journal is to improve the management of facilities and infrastructure in optimizing the teaching and learning process in Islamic religious education. The method used is descriptive analysis using various literature sources and articles as material for analyzing research problems. The result of this work is that management of educational facilities and infrastructure is a vital process that supports successful learning by maximizing the function of each school facility to achieve educational goals efficiently. This process is regulated through the principles of goal achievement, efficiency, administration and clarity of responsibility. The management stages include planning, procurement, distribution, inventory, maintenance, storage and deletion, all of which aim to maintain the quality and availability of facilities and infrastructure. The principal plays a key role in implementing these management principles effectively, supported by the deputy principal, staff, teachers and students in the management process. Teachers participate in planning needs, utilizing and maintaining infrastructure to improve the quality of learning. Collaboration and coordination between all related parties in schools is an important factor in effective management of facilities and infrastructure. With good management, educational facilities and infrastructure can be maintained and utilized optimally. This directly contributes to creating a conducive learning environment and improving the quality of education.